Phenotyping airways disease: an A to E approach. - Gonem, S; Raj, V; Wardlaw, A; Pavord, I; Green, R; Siddiqui, S (2012)
The airway diseases asthma and chronic obstructive pulmonary disease (COPD) are heterogeneous conditions with overlapping pathophysiological and clinical features. It has previously been proposed that this heterogeneity may be characterized in terms of five relatively independent domains labelled from A to E, namely airway hyperresponsiveness (AHR), bronchitis, cough reflex hypersensitivity, damage to the airways and surrounding lung parenchyma, and extrapulmonary factors. Airway hyperresponsiveness occurs in both asthma and COPD, accounting for variable day to day symptoms, although the mechanisms most likely differ between the two conditions. Bronchitis, or airway inflammation, may be predominantly eosinophilic or neutrophilic, with different treatments required for each. Cough reflex hypersensitivity is thought to underlie the chronic dry cough out of proportion to other symptoms that can occur in association with airways disease. Structural changes associated with airway disease (damage) include bronchial wall thickening, airway smooth muscle hypertrophy, bronchiectasis and emphysema. Finally, a variety of extrapulmonary factors may impact upon airway disease, including rhinosinusitis, gastroesophageal reflux disease, obesity and dysfunctional breathing. This article discusses the A to E concept in detail and describes how this framework may be used to assess and treat patients with airway diseases in the clinic.